Career future perceptions of university students with disabilities: a cross-sectional study in Turkiye - Karaca, Esra; Baykara Mat, Seda Tugba; Bastarcan, Cisem (Frontiers in Education, 2026)
Career futures of disabled students in Turkiye University students with disabilities often face unique barriers when envisioning and preparing for their career futures, making it important to understand the factors shaping their perceptions. This cross-sectional descriptive study investigated the career future perceptions of 121 disabled students enrolled at a private university in Istanbul, Türkiye. Data were collected through a demographic information form and the Career Future Scale (CFS), which measures adaptability, optimism, and perceived knowledge. Statistical analyses included descriptive statistics, Pearson correlation, independent t-tests, one-way ANOVA, and post-hoc tests. The mean total CFS score was 85.26 ± 15.61, with subscale means of 38.26 ± 8.25 for adaptability, 38.29 ± 7.69 for optimism, and 8.72 ± 2.96 for perceived knowledge. Significant differences emerged across demographic and disability-related variables: age and disability type were associated with total scores; age, living arrangement, disability type, and severity influenced adaptability; age and disability type influenced optimism; and age, gender, region of upbringing, and disability type influenced perceived knowledge. These findings highlight the importance of tailored career counseling, mentorship, and accessible resources to support the career development and equity of disabled university students.